"Gebah Sepah" (Assertive Training) Program to Improve Anti-Marital Sex Assertiveness - Mariani, Pebri; Sari, Fulziah Alwita; Putri, Nabilla Maulina; Noni, Noni; Rakiah, Rakiah (Psikologiya Journal, 2024)
Premarital sexual behavior is currently an issue for Indonesian teenagers because teenagers are now easy to follow romantic invitations from the opposite sex, premarital sex on the grounds that they already like each other and are mutually beneficial and love each other. Teenagers do not know that premarital sex is behavior that is bad for themselves. The cause of premarital sexual behavior in adolescents is because they do not have a positive assessment of themselves and others and lack the confidence to express their thoughts effectively. Following up on this, the researchers conducted the GEBAS SEPAH program because it can improve the assertiveness behavior of anti-marital sex teenagers through Assertive training. "GEBAS SEPAH" is an acronym for "Generation Free of Premarital Sex". The method of implementing this activity is preparation and selection of participants, debriefing, and implementation of activities. This program uses assertive training through the lecture method to educate adolescents to be able to express themselves. This program aims to train adolescents to be able to express themselves as they are without feeling afraid and pressured by others, and to be able to reject everything that is considered not in accordance with themselves. Based on the service that has been carried out by researchers, there is a significant increase in assertive behavior in students of class XI Language SMAN 3 Bukittinggi. This shows that assertive training given to students to prevent premarital sexual behavior is effective in increasing assertive behavior.